FAKTOR - FAKTOR YANG MEMPENGARUHI NIAT PEMBELIAN PELANGGAN PADA E-COMMERCE DI INDONESIA - Neria Anaya; Hendro Lukman; Juni Simina (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is empirically prove whether there is an influence between Ease of Use, Usefulness, Security, Convenience, and Website Quality on Customer Purchase Intentions in E-commerce in Indonesia. Sampling technique through google form using convenience sampling. The total sample is 119. The data is processed using SmartPLS with multiple regression analysis method. The results of the analysis of this study are Ease of Use, Usefulness, Security, and Convenience are not significant and have a negative effect on Customer Purchase Intentions, while Website Quality is significant and has a positive effect on Customer Purchase Intentions. The implication of this research is that strategies need to be improved to website quality in terms of satisfaction, usefulness, security, and convenience.